Auroville, une utopie spirituelle en contexte de mondialisation - Obadia, Lionel (Anthropologica, 2023)
The community of Auroville in southern India is built around a so-called “spiritual” project. Nonetheless, the nature, contours and manifestations of a coherent and socially shared spirituality system prove difficult to uncover due to the complexity of the ways in which the actual term “spirituality” is theorized (if it even is) in the core documents of the township’s founders and its scholars, and above all else, mobilized in the discourse of ordinary residents. An ethnography of Aurovilians’ concrete practices, conducted between 2013 and 2018 on the basis of their actions (productive or labour-related), their rituals and their subjective experiences, allows us, however, to conjure up spiritual modalities that are unevenly distributed both socially and geographically, because Auroville is also a reticular and deterritorialized community. The article questions the notion of spirituality in a context where it appears paradoxically relevant at the empirical level but imprecise at the theoretical level. An imprecision that, in this particular context, is more an advantage than a theoretical weakness.